Les débuts du surréalisme français : reconnaissance littéraire et reconnaissance médiatique - Paul Aron (Carnets, 2017)
This article deals with the role of the daily paper Comoedia in the formation of the first surrealist group. It shows that the stands of the former Dadaists often expressed themselves in the popular press, and not only in the small reviews of the restricted literary field. On the methodological plan, the article pleads in favor of a sociological analysis of the avant-garde in connection with the other sectors of the literary production, which were connected to the international and intermedia contacts of the writers.